Two new species of Lamiinae (Coleoptera: Cerambycidae) from the Neotropical Region - Bezark, Larry G.; Galileo, Maria Helena M.; Santos-Silva, Antonio (Zootaxa, 2016)
Two new species of Cerambycidae are described from the Neotropical Region: Estoloderces obliquus sp. nov. from Costa Rica and Stereomerus swifti sp. nov. from Ecuador.